2018
DOI: 10.1016/j.jor.2018.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Topical vancomycin and its effect on survival and migration of osteoblasts, fibroblasts, and myoblasts: An in vitro study

Abstract: The purpose of this study was to examine the influence of topical vancomycin on cell migration and survival of tissue healing cells. Human osteoblasts, myoblasts and fibroblasts were exposed to vancomycin at concentrations of 1, 3, 6, or 12 mg/cm for either a 1-h or 48-h (continuous) duration. Continuous exposure to all vancomycin concentrations significantly reduced cell survival (<22% cells survived) and migration in osteoblasts and myoblasts (P < 0.001). 1-h vancomycin exposure reduced osteoblast and myobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…They found that as CHX concentration increased there was a significant (p<0.001) difference in fibroblast proliferation - even at their lowest tested concentration (1%), exposure to CHX resulted in in vitro fibroblast survival of 51.7% compared to no exposure 33 . The dose-dependent cytotoxicity of CHX on fibroblasts, myoblasts, and osteoblasts is not a unique property of CHX; prior in vitro studies have demonstrated that dilute povidone-iodine and topical vancomycin powder, also used for prevention of surgical site infections, have similarly specific dose-dependent and time-dependent cytotoxicity profiles on fibroblasts, myoblasts, and osteoblasts, as measured via the scratch test and Cell Counting Kit-8 cell survival assay 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…They found that as CHX concentration increased there was a significant (p<0.001) difference in fibroblast proliferation - even at their lowest tested concentration (1%), exposure to CHX resulted in in vitro fibroblast survival of 51.7% compared to no exposure 33 . The dose-dependent cytotoxicity of CHX on fibroblasts, myoblasts, and osteoblasts is not a unique property of CHX; prior in vitro studies have demonstrated that dilute povidone-iodine and topical vancomycin powder, also used for prevention of surgical site infections, have similarly specific dose-dependent and time-dependent cytotoxicity profiles on fibroblasts, myoblasts, and osteoblasts, as measured via the scratch test and Cell Counting Kit-8 cell survival assay 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that 1 h vancomycin exposure reduced osteoblast and myoblast survival and migration only at the highest dosage (12 mg/cm 2 ). Conversely, a prolonged vancomycin exposure significantly impaired both survival and migration in all cell types at all concentrations tested [ 34 ]. According to our results, it may be reasonable to reduce vancomycin concentration for graft soaking under 5 mg/mL to reduce the risk of graft damage without affecting antimicrobial efficacy, as the MIC for most bacteria involved in post-ACLR septic arthritis is approximately 2 mg/mL [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies on cellular toxicity of vancomycin have been conducted on relevant cell types within a joint. 1,3,9,19 Bariteau et al 3 found that exposing human mesenchymal stromal cells (hMSCs) to 5000 µg/mL vancomycin for 3 days resulted in significantly decreased cell viability, proliferation, and mineralization. Chu et al 9 established a dose-dependent increase in cell death for hMSCs exposed to vancomycin for 24 hours, starting at 400 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that various cell types respond differently to antibiotic exposure. Liu et al 19 exposed osteoblasts, fibroblasts, and myoblasts to vancomycin for a short duration (1 hour) or continuous duration (48 hours). They found that for short durations, osteoblast and myoblast survival and migration were not affected by vancomycin, except for at the highest concentration of 12 mg/mL.…”
Section: Discussionmentioning
confidence: 99%